Editor: Looking Back and Thinking Ahead for Strengthening the Profile Journal - Melba Libia Cárdenas; María Claudia Nieto-Cruz (Universidad Nacional de Colombia, 2020)
Last February we held the XV PROFILE Symposium, an annual local event aimed at inviting teachers of English from different backgrounds to reflect on our profession, to share research results and innovations, and to highlight the importance of doing research. We also took the opportunity to encourage the participants to share their findings through publishing.